X-ray excited luminescence spectroscopy and imaging with NaGdF4:Eu and Tb. Issue 50 (24th September 2021) - Ranasinghe, Meenakshi; Arifuzzaman, Md.; Rajamanthrilage, Apeksha C.; Willoughby, W. R.; Dickey, Ashley; McMillen, Colin; Kolis, Joseph W.; Bolding, Mark; Anker, Jeffrey N.
Abstract : We synthesized and characterized Eu and Tb doped NaGdF4 nanophosphors which generate visible light when excited by a focused X-ray beam. High resolution images were acquired through tissue by measuring light intensity vs. X-ray beam position. Abstract : X-ray excited optical luminescence from nanophosphors can be used to selectively generate light in tissue for imaging and stimulating light-responsive materials and cells. Herein, we synthesized X-ray scintillating NaGdF4 :Eu and Tb nanophosphors via co-precipitate and hydrothermal methods, encapsulated with silica, functionalized with biotin, and characterized by X-ray excited optical luminescence spectroscopy and imaging. The nanophosphors synthesized by co-precipitate method were ∼90 and ∼106 nm in diameter, respectively, with hydrothermally synthesized particles showing the highest luminescence intensity. More importantly, we investigated the effect of thermal annealing/calcination on the X-ray excited luminescence spectra and intensity. At above 1000 °C, the luminescence intensity increased, but particles fused together. Coating with a 15 nm thick silica shell prevented particle fusion and enabled silane-based chemical functionalization, although luminescence decreased largely due to the increased mass of non-luminescent material. We observed an increase in luminesce intensity with temperature until at 400 °C. At above 600 °C, NaGdF4 :Eu@SiO2 converts to NaGd9 Si6 O26 :Eu, an X-ray scintillator brighter than annealed NPs at 400 °C and dimmer than NPs synthesized using the hydrothermal method. The particles generate light through tissue and can be selectively excited using a focused X-ray source for imaging and light generation applications. The particles also act as MRI contrast agents for multi-modal localization.